2011
DOI: 10.3109/14767058.2010.545925
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of C-reactive protein levels in pregnancies with retained and removed intrauterine device

Abstract: Serum CRP concentrations are increased in pregnant women with retained IUD. Our findings also suggest that the pregnancies with retained IUDs that are not removed are at increased risk for adverse pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Although the outcome had been favorable, retained IUD are also associated, although rarely, with fetal and amniotic candida infections [13]. In a more recent review of 30 cases, the rates of miscarriage, preterm rupture of membranes, placental abruption, and preterm delivery were signiWcantly higher in pregnant women with retained IUD compared with pregnancies after IUD removal in early pregnancy [14]. So it is advisable to remove an IUD as soon as possible if a woman becomes pregnant.…”
Section: Discussionmentioning
confidence: 97%
“…Although the outcome had been favorable, retained IUD are also associated, although rarely, with fetal and amniotic candida infections [13]. In a more recent review of 30 cases, the rates of miscarriage, preterm rupture of membranes, placental abruption, and preterm delivery were signiWcantly higher in pregnant women with retained IUD compared with pregnancies after IUD removal in early pregnancy [14]. So it is advisable to remove an IUD as soon as possible if a woman becomes pregnant.…”
Section: Discussionmentioning
confidence: 97%
“…However, this was the first meta-analysis which summarized all studies focusing on IUD removed, retained, and no IUD to the pregnancy outcome. Of all studies that included IUD retained and removed, only studies by Seval et al 14 and Ruya et al 13 used ultrasound examination to reveal visible copper IUD in the uterine cavity. After this examination, Ruya et al 13 and Hadas et al 8 showed explicitly that IUD removal was performed in the early gestation, namely first 12 weeks of gestation (trimester 1).…”
Section: Discussionmentioning
confidence: 99%
“…Of all studies that included IUD retained and removed, only studies by Seval et al 14 and Ruya et al 13 used ultrasound examination to reveal visible copper IUD in the uterine cavity. After this examination, Ruya et al 13 and Hadas et al 8 showed explicitly that IUD removal was performed in the early gestation, namely first 12 weeks of gestation (trimester 1). Meanwhile, other studies did not mention clearly the time of IUD removal.…”
Section: Discussionmentioning
confidence: 99%
“…No evidence of chorioamnionitis was observed in our study, which could be due to the fact that the IUD had been removed in almost all of the cases, contrary to the Ganer et al study, who reported that the incidence of chorioamnionitis was significantly higher in both the retained and removed IUD groups, compared to the no IUD group. 10 Wegmann et al proposed that in pregnancy, there are pro-inflammatory cytokines and the shifting from lymphocyte T helper cell 1 to a T helper cell 2 that functionally maintain pregnancy and do not permit the fetus to be rejected; 7 since IUD causes inflammation in the endometrial surfaces and disturbs implantation, due to increase in inflammatory markers in IUD group, 8 it could be proposed that inflammation and preterm premature rupture of membranes are expected in these conditions.…”
Section: Differences In Results and Conclusion In Relation To Other mentioning
confidence: 99%
“…5,7,12 Moreover, Deveer et al found that the risk of miscarriage increased significantly when the IUD is retained, compared to when it is removed. 8 Brahmi et al demonstrated that if the IUD is left in the uterus, the rate of miscarriage, preterm labour, and chorioamnionitis are increased. 5 In the present study, the number of cases whose pregnancies with retained IUDs was too low; of these most had higher rates of induced abortions, compared to the removed IUD group.…”
Section: Differences In Results and Conclusion In Relation To Other mentioning
confidence: 99%